2021
DOI: 10.1021/acs.analchem.1c00515
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Measurement of Both SARS-CoV-2 RNA and Antibodies from Saliva

Abstract: Tests for COVID-19 generally measure SARS-CoV-2 viral RNA from nasal swabs or antibodies against the virus from blood. It has been shown, however, that both viral particles and antibodies against those particles are present in saliva, which is more accessible than both swabs and blood. We present methods for highly sensitive measurements of both viral RNA and antibodies from the same saliva sample. We developed an efficient saliva RNA extraction method and combined it with an ultrasensitive antibody test based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…The most widely used current diagnostic method, real-time polymerase chain reaction (RT-PCR) testing, is the gold standard and the most accessible diagnostic tool for SARS-CoV-2 identification. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…The most widely used current diagnostic method, real-time polymerase chain reaction (RT-PCR) testing, is the gold standard and the most accessible diagnostic tool for SARS-CoV-2 identification. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional studies on larger cohorts, as well as systematical comparisons to additional available serological tests are needed. Finally, combined single-molecule based detection of both viral RNA and antibodies was recently demonstrated by Ter-Ovanesyan and colleagues for saliva samples [28]. The use of saliva samples which contain both viral RNA and antibodies against viral particles holds great potential and can be further explored for analysis by our adaptable single-molecule platform.…”
Section: Discussionmentioning
confidence: 92%
“…Saliva represents an appealing biofluid for non-invasive SARS-CoV-2 antibody detection, with the ease of self-collection and is pain-free. Previous work has shown that IgG antibodies in saliva correlated well with those in blood for various infectious diseases including SARS-CoV-2 11,[23][24][25][26][27][28][29][30][31][32] . However, a challenge of saliva sample testing is the much lower concentration of antibodies present than in serum, plasma and blood, demanding high analytical sensitivity of detection methods 33 .…”
Section: Introductionmentioning
confidence: 89%